Systemic Factors Leading to Incarceration and Its Impact on Marginalized Communities - Shenyu Yin (Studies in Law and Justice, 2024)
This paper critically examines the systemic factors contributing to mass incarceration in the United States, with a particular focus on the overrepresentation of marginalized groups such as African American, Hispanic, and economically disadvantaged individuals. Drawing on recent quantitative data and literature review, the study explores how income inequality, racial disparity, family structure, and policing practices contribute to the cycles of incarceration. The research highlights the systemic inequalities that lead to harsher sentencing, over-policing, and limited post-incarceration opportunities for marginalized communities. By using multivariate regression analysis, a strong correlation between indicators of inequality and rates of crime was shown, which perpetuates systemic injustice in these communities. The findings suggest that while recent reforms—such as the reduction of mandatory minimum sentencing—have had a modest impact on incarceration rates, they fall short of addressing the deeper racial and economic inequalities that drive mass incarceration. This study advocates for comprehensive criminal justice reform beyond surface-level decriminalization efforts to address the root causes of inequality, particularly economic investment, community-based policing, and rehabilitation-focused prison systems.